Studies in Islamic art - Pinder-Wilson, Ralph (Selected studies in the history of art, 1985)
This volume brings together twenty-four of Dr. Pinder-Wilson's studies on Islamic art, published over the last thirty years. These deal principally with the decorative arts - lustre pottery, bronze, jade and glass - a field in which the author is an eminent authority. The objects covered range from earky Islamic glass and lustre ware to the ivories produced in Norman Sicily and later Persian bronzes. The art of Mughal India and Afghanistan is also covered, in a number of important studies on manuscripts produced for Persian and Mughal rulers from the fifteenth to the seventeenth centuries. Two major papers reprinted here range outside the usual field of the art historian. The first, a study of the Malcolm celestial globe, explores the history and iconography of Islamic depictions of the constellations ; the second, a study of the Persian garden from the Achaemenid to the Qajar period, examins the textual evidence, and discusses the influence of this tyoe of garden on the visual arts.